O QUE É PARTIDO DE PROJETO? - Faccioli GABRIEL, Marcos (Revista Tópos, 2013)
A expressão “partido de projeto” é de uso corrente entre arquitetos brasileiros e já ganhou lugar nos dicionários da língua. Contudo, não se encontra na bibliografia uma caracterização formal enquanto conceito. Neste estudo, investigamos o sentido da mesma enquanto designação do modo de operar que distingue a arquitetura das disciplinas universitárias com as quais coopera na construção do ambiente humano. Enquanto na tecnologia deve haver uma correspondência ponto a ponto entre as características do objeto e a performance esperada do mesmo, no projeto de arquitetura isto é pouco provável pois este não pode satisfazer no mesmo grau todos os critérios que sobre ele incidem, sendo o “partido do projeto” aquele ato de escolha de prioridades funcionais, tecnológicas ou estéticas de modo a obter um objeto possível e cuja significação supera qualquer tabela prévia de desempenhos. Palavras-chave : projeto arquitetônico, projeto tecnológico, arquitetura, engenharia, estética da arquitetura. Abstract “Partido de projeto” is a current expression amongst brazilian architects with no English equivalent. So usual it has become that dictionaries have already granted a place to it. However, nowhere in the professional literature a formal conceptualization thereof can be found. We here undertake to investigate its meaning as the operative way which is peculiar to architecture and sets it off all disciplines with which it shares the building of human environment. Whereas in technology one can always expect a one to one relationship between every characteristic of the object and its assigned performance, in the architectural design such mode of correspondence is not supposed to be matched up, for the latter can’t meet up all the requirements that bear on it to the same extent and with equal emphasis. The “Partido de projeto” stands out then as the act of choice by way of which some requirements are brought to the fore, be them of functional, constructive or of aesthetic nature, so as to lead up to a possible object, whereas other aspects are meant to play a secondary role and to stand in the background. The unity that turns out of the processes however bears a signification to itself that can’t be put forth in advance by any formal set of requirements. Keywords : architectural design, technological design, engineering, architecture, architectural aesthetics.